2005
DOI: 10.1111/j.1365-2710.2004.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive use of atypical antipsychotics and anticholinergic drugs among patients with schizophrenia

Abstract: As the use of anticholinergics is a proxy for the presence of EPS, these findings suggest that risperidone may be more associated with EPS than olanzapine. However, to assess the benefits and side effects associated with olanzapine or risperidone, future research needs to examine various patient outcomes resulting from the initiation of each drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…However, considering the inappropriateness of the conventional approach in measuring treatment persistence as well as the limitations of the present study, more research is needed to examine the extent to which adjunctive use of other agents, a common practice among patients with schizophrenia (Ren et al 2004), will influence levels of treatment persistence. Future research should also assess the impact of poor treatment persistence on a wide spectrum of patient outcomes (Ren et al 2005b). A more comprehensive assessment using appropriate analytic methods should provide physicians with a better knowledge about treatment persistence associated with different antipsychotic agents and help them make prescription choices that will ultimately improve the care of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the inappropriateness of the conventional approach in measuring treatment persistence as well as the limitations of the present study, more research is needed to examine the extent to which adjunctive use of other agents, a common practice among patients with schizophrenia (Ren et al 2004), will influence levels of treatment persistence. Future research should also assess the impact of poor treatment persistence on a wide spectrum of patient outcomes (Ren et al 2005b). A more comprehensive assessment using appropriate analytic methods should provide physicians with a better knowledge about treatment persistence associated with different antipsychotic agents and help them make prescription choices that will ultimately improve the care of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…In a third study, Ren et al [2005b] reported that risperidone initiators had significantly more use of at least one anticholinergic agent adjunctively compared to those initiated on olanzapine, and that those on either olanzapine or risperidone stayed on the targeted medication significantly longer than those who were not prescribed any anti-cholinergic agent (Po0.05). Results were important for understanding clinical practices for future development of medication guidelines.…”
Section: Utilization Of Services and Medication Therapymentioning
confidence: 95%
“…In other medication studies involving patients diagnosed with schizophrenia and their anti-psychotic use, Ren et al [2002bRen et al [ , 2004Ren et al [ , 2005b merged patientreported HRQoL data (VR-36) and utilization of psychiatric services with medication history that includes dosage and duration of use on the basis of 89,107 subjects. Using a cohort design, results show that olzanzapine and risperidone users were associated with different sociodemographic characteristics; those on olanzapine compared to those on risperidone were younger (Po0.001), Hispanic (Po0.001), with fewer medical co-morbidities and a lower body mass index (Po0.05).…”
Section: Utilization Of Services and Medication Therapymentioning
confidence: 99%
“…Similar observation was observed in a study by Ren et al where when anti-C agents were used concomitantly with atypical anti-Ps, patients tend to stay on target drug significantly longer than those who did not use any anticholinergic agents. 12 The average number of drugs per prescription is an important index of the scope for review and educational intervention in prescribing practices. The average number of drugs per prescription in our study is 4.02, higher compared to studies by Shankar and Roy, Piparva et al and Dutta et al…”
Section: 9mentioning
confidence: 99%